The role of HDAC3 in inflammation: mechanisms and therapeutic implications - Watson, Noah; Kuppuswamy, Sivaraman; Ledford, William Luke; Sukumari-Ramesh, Sangeetha (Frontiers in Immunology, 2024)
Histone deacetylases (HDACs) are critical regulators of inflammatory gene expression, and the efficacy of pan-HDAC inhibitors has been implicated in various disease conditions. However, it remains largely unclear how HDACs precisely regulate inflammation. To this end, evaluating the isoform-specific function of HDACs is critical, and the isoform-specific targeting could also circumvent the off-target effects of pan-HDAC inhibitors. This review provides an overview of the roles of HDAC3, a class I HDAC isoform, in modulating inflammatory responses and discusses the molecular mechanisms by which HDAC3 regulates inflammation associated with brain pathology, arthritis, cardiovascular diseases, lung pathology, allergic conditions, and kidney disorders. The articles also identify knowledge gaps in the field for future studies. Despite some conflicting reports, the selective inhibition of HDAC3 has been demonstrated to play a beneficial role in various inflammatory pathologies. Exploring the potential of HDAC3 inhibition to improve disease prognosis is a promising avenue requiring further investigation.